2021
DOI: 10.5539/elt.v14n7p107
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception towards Formative Assessment in Saudi Universities’ Context: A Review of Literature

Abstract: Formative assessment has received considerable attention among scholars around the world. In Saudi Arabia, formative assessment is perceived as a promising opportunity for improving learning outcomes. The review of literature presents formative assessment as a serious issue that can affect students’ outcomes. In particular, teachers’ perception is an important factor that determines their willingness to apply specific assessment strategies in class. According to the findings, formative asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…From these results, we can conclude that students have a very positive attitude towards the teacher and the class. This result is also in accordance with the results of previous studies which showed a significant difference in the use of formative tests in favour of the experimental group (Van der Kleij et al, 2018;Ismail & Tini, 2020;Lui & Andrade, 2022;Voinea, 2018;Evans et al, 2014;Dayal, 2021;Gezer et al, 2021;Alsubaiai, 2021).…”
Section: Resultssupporting
confidence: 93%
“…From these results, we can conclude that students have a very positive attitude towards the teacher and the class. This result is also in accordance with the results of previous studies which showed a significant difference in the use of formative tests in favour of the experimental group (Van der Kleij et al, 2018;Ismail & Tini, 2020;Lui & Andrade, 2022;Voinea, 2018;Evans et al, 2014;Dayal, 2021;Gezer et al, 2021;Alsubaiai, 2021).…”
Section: Resultssupporting
confidence: 93%
“…In a previous study, Alsubaiai (2021) argued that teachers' perception of formative assessment determines whether they give the assessment and the type of strategies to use. The study also observed that teachers' teaching experience and education level influence their perceptions of formative assessment.…”
Section: Language Assessment and Online Assessmentmentioning
confidence: 99%
“…Bartz (2017) and Bulunuz & Bulunuz (2013) emphasize its role in tracking learner progress and understanding their knowledge acquisition. However, its effectiveness can be compromised by teachers' limited appreciation of its value (Alsubaiai, 2021;Ahmedi, 2019;Jawad, 2020). Clark (2012) associates formative assessment with self-regulated learning (SRL), linked to higher academic achievement and learner motivation.…”
Section: The Purpose and Importance Of Formative Assessment In Educationmentioning
confidence: 99%